Molecular mechanisms of APC/C release from spindle assembly checkpoint inhibition by APC/C SUMOylation - Yatskevich, Stanislau (Cell Rep, 2021)
The anaphase-promoting complex/cyclosome (APC/C) is an E3 ubiquitin ligase that controls cell cycle transitions. Its regulation by the spindle assembly checkpoint (SAC) is coordinated with the attachment of sister chromatids to the mitotic spindle. APC/C SUMOylation on APC4 ensures timely anaphase onset and chromosome segregation. To understand the structural and functional consequences of APC/C SUMOylation, we reconstituted SUMOylated APC/C for electron cryo-microscopy and biochemical analyses. SUMOylation of the APC/C causes a substantial rearrangement of the WHB domain of APC/C’s cullin subunit (APC2(WHB)). Although APC/C(Cdc20) SUMOylation results in a modest impact on normal APC/C(Cdc20) activity, repositioning APC2(WHB) reduces the affinity of APC/C(Cdc20) for the mitotic checkpoint complex (MCC), the effector of the SAC. This attenuates MCC-mediated suppression of APC/C(Cdc20) activity, allowing for more efficient ubiquitination of APC/C(Cdc20) substrates in the presence of the MCC. Thus, SUMOylation stimulates the reactivation of APC/C(Cdc20) when the SAC is silenced, contributing to timely anaphase onset.